2012
DOI: 10.3389/fpsyg.2012.00195
|View full text |Cite
|
Sign up to set email alerts
|

Theta-Modulated Gamma-Band Synchronization Among Activated Regions During a Verb Generation Task

Abstract: Expressive language is complex and involves processing within a distributed network of cortical regions. Functional MRI and magnetoencephalography (MEG) have identified brain areas critical for expressive language, but how these regions communicate across the network remains poorly understood. It is thought that synchronization of oscillations between neural populations, particularly at a gamma rate (>30 Hz), underlies functional integration within cortical networks. Modulation of gamma rhythms by theta-band o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 100 publications
(162 reference statements)
3
31
0
Order By: Relevance
“…Group source analysis showed low-beta [13, 23] Hz ERD at left inferior frontal and posterior temporal regions, consistent with previous MEG expressive language studies (Singh et al, 2002; Hirata et al, 2004; Kadis et al, 2008, 2011; Ressel et al, 2008; Pang et al, 2011; Doesburg et al, 2012). Whole brain connectivity based on PLV metric derived from broad-band (3–30 Hz) sources suggested prominent connectivity at left perisylvian sites (Figure 1B) and hubs in left prefrontal regions (Figure 1C).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Group source analysis showed low-beta [13, 23] Hz ERD at left inferior frontal and posterior temporal regions, consistent with previous MEG expressive language studies (Singh et al, 2002; Hirata et al, 2004; Kadis et al, 2008, 2011; Ressel et al, 2008; Pang et al, 2011; Doesburg et al, 2012). Whole brain connectivity based on PLV metric derived from broad-band (3–30 Hz) sources suggested prominent connectivity at left perisylvian sites (Figure 1B) and hubs in left prefrontal regions (Figure 1C).…”
Section: Discussionsupporting
confidence: 88%
“…More recently, researchers have begun to use sophisticated analytic strategies such as functional and effective connectivity analysis to explore regional interactions for language (Bitan et al, 2005, 2006; Sonty et al, 2007; Allen et al, 2008; Leff et al, 2008; Schofield et al, 2009; David et al, 2011; Doesburg et al, 2012, 2015; Verly et al, 2014; Kadis et al, 2015; Xiao et al, 2016). In our recent MEG study of verb generation in children, we observed frequency dependent patterns of connectivity together with an increased number of suprathreshold effective (directed) connections with age, even though the extent of the network decreased and became increasingly left lateralized with age (Kadis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Task-dependent increases in inter-regional synchronization have been associated with numerous cognitive processes (see Uhlhaas et al, 2009a;Palva et al, 2012 for reviews) including both expressive and receptive language (Doesburg et al, 2008(Doesburg et al, , 2012 and letter processing (Herdman, 2011). Presently, we establish the normative developmental trajectory of inter-regional network synchronization throughout childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of neural oscillations, and their coordination across brain areas, have been linked to expressive language, receptive language, and the interactions between language networks and brain regions mediating other cognitive and perceptual abilities (i.e. Bastiaansen et al, 2005;Bedo et al, 2014;Bögels et al, 2014;Doesburg et al, 2008Doesburg et al, , 2012Ewald et al, 2012;Hermes et al, 2014;Mellem et al, 2013;Piai et al, 2013;Weiss & Mueller 2012), and local neural oscillations have been related to the encoding of speech sounds as well as the development of language abilities during infancy and early childhood (Benasich et al, 2008;Gou et al, 2011). Whether inter-regional coherence changes throughout childhood and adolescence, as well as if such changes are related to the development of language abilities, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, gamma power increases more in response to action verbs than object nouns over motor cortices (Pulvermiiller et al, 1996) and increases over both left and right inferior frontal areas during verb generation tasks (Doesburg, Vinette, Cheung, & Pang, 2012). Conversely, gamma power decreases are observed in response to incongruent or unrelated informa tion in ongoing sentences (Bastiaansen et al, 2010;Hagoort et al, 2004;Hald et al, 2006;Penolazzi, Angrilli, & Job, 2009;Wang et al, 2012).…”
mentioning
confidence: 96%